Decolonizing the Curriculum? Unsettling possibilities for performance training - O'Shea (University of California – UCLA, Los Angeles, United States of America), Janet (Revista Brasileira de Estudos da Presença, 2022)
TThis essay problematizes the term ‘decolonization’ as applied to university dance and performance curricula. It does so via Eve Tuck and K. Wayne Yang’s (2012) argument that colonization is rooted in a worldview that positions beings as exploitable things. Addressing efforts to foster diversity within studio training, choreography, and scholarship, the casualization of labor within university departments is also examined. The essay considers the structure of the university as both a colonial and corporate entity, signaling its relationship to the precarity of neoliberalism. The paper concludes by suggesting that arts and humanities scholarship and teaching create opportunities for alternate ways of living and interacting beyond neoliberal, neocolonial paradigms.